2015
DOI: 10.1189/jlb.4a0815-346r
|View full text |Cite
|
Sign up to set email alerts
|

TLR9 is required for MAPK/NF-κB activation but does not cooperate with TLR2 or TLR6 to induce host resistance to Brucella abortus

Abstract: Brucella abortus is a Gram-negative intracellular bacterial pathogen that causes a zoonosis of worldwide occurrence, leading to undulant fever in humans and abortion in domestic animals. B. abortus is recognized by several pattern-recognition receptors triggering pathways during the host innate immune response. Therefore, here, we determined the cooperative role of TLR9 with TLR2 or TLR6 receptors in sensing Brucella Furthermore, we deciphered the host innate immune response against B. abortus or its DNA, emph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 44 publications
1
42
0
Order By: Relevance
“…The recognition of B. abortus by innate immune receptors results in the activation of different signaling pathways, culminating in the expression of several proinflammatory genes . We next assessed the potential role of NLRP12 in regulating NF‐κB and MAPK signaling pathways in BMDMs upon B. abortus infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The recognition of B. abortus by innate immune receptors results in the activation of different signaling pathways, culminating in the expression of several proinflammatory genes . We next assessed the potential role of NLRP12 in regulating NF‐κB and MAPK signaling pathways in BMDMs upon B. abortus infection.…”
Section: Resultsmentioning
confidence: 99%
“…TLRs are transmembrane receptors, that recognize and bind pathogen‐associated molecular patterns (PAMPs), resulting in signal transduction and translocation of NF‐κB transcription factor to the nucleus and phosphorylation of mitogen‐ activated protein (MAP) kinases p38, JNK and ERK . Our laboratory and others have described the involvement of several TLRs and TLRs‐associated pathways, such as TLR9 and MyD88, in the recognition of B. abortus .…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that MyD88 is responding to Brucella infection of the joints, but the nature of the reacting cell types remains unknown. Numerous cell types in the joint, including macrophages, dendritic cells, synovial fibroblasts, chondrocytes, endothelial cells, and fibroblast-like synoviocytes, are capable of responding to exogenous and endogenous TLR ligands and could be mediating inflammation in our model (28,(54)(55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…This signaling can result in arthritis and osteoclastogenesis in murine models of bacterium-induced focal complications (25)(26)(27). Host cells reportedly recognize Brucella through TLR2, TLR4, TLR6, and TLR9 (28)(29)(30)(31)(32). To determine if MyD88 signaling is important for Brucella-induced arthritis, we investigated joint inflammatory responses in MyD88 Ϫ/Ϫ mice following footpad infection with Brucella.…”
mentioning
confidence: 99%
“…Furthermore, Gomes et al, 2015 [25] revealed that CpG motifs derived from Brucella DNA are involved in activation of host innate immune response through the TLR9 receptor. TLR9 plays an important role in initial control of infection by Brucella abortus [26].…”
Section: Introductionmentioning
confidence: 99%